2012
DOI: 10.1002/uog.11074
|View full text |Cite
|
Sign up to set email alerts
|

Role of uterine artery Doppler in the management of uterine leiomyoma by arterial embolization

Abstract: Objectives To study Doppler changes in the uterine artery immediately following and 3 months after uterine artery embolization (UAE)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Showing that fibroid vascularization decreases after UPA therapy is not only an interesting scientific observation but also provides a theoretical rationale for future studies that could investigate the possible relationship between initial fibroid vascularization and outcome of UPA treatment. Moreover, evaluating changes in uterine artery blood flow enables the prediction of fibroid volume reduction after UAE, therefore perhaps it will be possible to predict the long‐term effects of UPA by assessing the changes in vascular indices following treatment. Finally, we present a new approach to 3D power Doppler indices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Showing that fibroid vascularization decreases after UPA therapy is not only an interesting scientific observation but also provides a theoretical rationale for future studies that could investigate the possible relationship between initial fibroid vascularization and outcome of UPA treatment. Moreover, evaluating changes in uterine artery blood flow enables the prediction of fibroid volume reduction after UAE, therefore perhaps it will be possible to predict the long‐term effects of UPA by assessing the changes in vascular indices following treatment. Finally, we present a new approach to 3D power Doppler indices.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that the amount of reduction in fibroid volume during the first year following UAE may predict long‐term outcome. Similarly, initial fibroid vascularization or changes in uterine artery blood flow after UAE may predict the decrease in fibroid volume after the procedure. UPA therapy decreases fibroid volume, but its impact on vascularity has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in fibroid vascularity after UAE seems to precede the decrease of fibroid volume at three months; indeed, fibroids without detectable vascularization are those with the most significant volume reduction (Tranquart et al, 2002). The RI of uterine arteries may predict volume reduction at three months after UAE since it is reported that a RI value between 0.82 and 0.88 immediately after the procedure is associated with a 38-61% reduction in fibroid volume at three months (Naguib et al, 2012). In addition, 3D Power Doppler fibroid vascularization parameters seem to reduce after three months from UAE (VI 1.44 vs. 0.12, FI 24.01 vs. 10.44, and VFI 0.24 vs. 0.01) (Czuczwar et al, 2015).…”
Section: Response To Therapymentioning
confidence: 99%
“…Directly after the procedure the following factors were of predictive value: when less than 90 % of the fi broids showed signs of infarction on the post-UAE MRI scan there was more chance of re-interventions [ 15 , 16 ]. Post-UAE fi broid volume at follow up was related to post-UAE dopplers (resistance index) directly after the procedure [ 17 ].…”
Section: Patient Selection and Prediction Of Uae Outcomementioning
confidence: 99%